WiMax Operator’s Manual Building 802.16 Wireless Networks (Second Edition) - Sweeney, Daniel (Apress, 2013)
The information in this book is distributed on an “as is” basis, without warranty. Although every precaution has been taken in the preparation of this work, neither the author(s) nor Apress shall have any liability to any person or entity with respect to any loss or damage caused or alleged to be caused directly or indirectly by the information contained in this work.